For immediate release : shape minds, build brands, and deliver results with game-changing public relations - Torossian, Ronn; Kelly, Karen, 1958- (Macmillan, 2021)
"It is essential that businesses know how to communicate quickly, often preemptively, and effectively to survive-and at a cost that is far lower than comparable marketing and ad campaigns. The first book by the owner of a top 50 PR agency, For Immediate Release, Ronn Torossian reveals how public relations can do just that-while also defining brands; helping companies and individuals court the press or avoid it; growing business without alienating loyal customers; resolving crises quickly; and improving first page results on the most powerful search engine in the world (Google). For Immediate Release will show you how to: Frame the debate and control the conversation Use new and old media in tandem to find your audiences and create highly personal, relevant impressions tailored for them Promote the interests of your brand or business; deter or potentially stop what is not in your interest Build on great press, and avoid or minimize bad press Ensure the first thing people see about your business or brand during an Internet search is exactly what you want them to see Handle a crisis in the most effective and efficient manner See the positive difference effective PR makes through compelling case studies-Louis Vuitton, Fubu, BP, Toyota, Philip Stein, Zappos, and interviews with experts including Dr. Keith Ablow, political strategists Frank Luntz, Roger Stone and Hank Sheinkopf, and many others-and your own business"--